Use of conditional inference trees for evaluating the effect of reclaimed asphalt pavement content and binder grade on the dynamic modulus of asphalt concrete mixtures - Yang, Jidong J.; Lakte, Pe-Tseskme A.; Kim, Sung-Hee (International Journal of Pavement Research and Technology, 2018)
Reclaimed asphalt pavement (RAP) has seen increasing use because it significantly reduces the paving cost, conserves energy, and protects the environment. This paper evaluates how RAP content and binder grade affect the dynamic modulus |E∗| of asphalt concrete mixtures. The mix design includes four RAP contents (0%, 15%, 25% and 30%) and three binder grades (PG64-22, PG67-22, PG76-22). Dynamic modulus tests were performed and |E∗| was measured at four levels of temperatures (40, 70, 100, 130 °F) and six loading frequencies (25, 10, 5, 1, 0.5, 0.1 Hz) in accordance with AASHTO T 342. Based on the test results, a conditional inference tree was estimated, which showed a higher level of RAP content or binder grade generally results in a higher |E∗|. Across the four levels of RAP contents, a significant increase in |E∗| occurred as RAP increased up to 30%. The hierarchical structure of the estimated conditional inference tree reveals the interplay between the two mix design variables (i.e., RAP content and binder grade) depending on the levels of loading frequency and temperature. In general, the binder grade has a stronger association with |E∗| than the RAP content when the reduced frequency is high while the RAP content has a stronger association with |E∗| than the binder grade when the reduced frequency is low. This implies that a balanced mix design should be sought in selecting proper levels of RAP content and binder grade subject to application contexts in terms of temperature and traffic loading.